Multi-Criteria, crosstalk-sensitive flexible topology approach for routing in SDM-EONs - Oliveira, Ramon Alves (2025)
In recent years, the demand for high-capacity, flexible optical networks has driven significant advancements in network design, especially within Space-Division Multiplexing Elastic Optical Networks (SDM-EONs). These networks are expected to efficiently handle the increasing volume of data traffic while minimizing issues such as inter-core crosstalk and request blocking, which can degrade performance. To address these challenges, we propose an RMSSA (Routing, Modulation, Spectrum, and Space Assignment) approach specifically for SDM-EONs. Our method dynamically calculates link-weight across the network topology by considering a combination of critical network factors, enabling a flexible topology that self-balances network load prior to every incoming resource request. Next, our approach maps all slots in the spectrum guaranteed to not disrupt already allocated light-paths, while being under the crosstalk threshold for any desired modulation format, which is enabled by the adoption of precise slice-based crosstalk estimation (PS-XT). This multi-criteria, crosstalk-aware routing strategy significantly reduces inter-core crosstalk, leading to more efficient resource utilization and a considerable reduction in request blocking, ultimately enhancing the overall performance and reliability of SDM-EONs. Our comparative results show average reductions in request blocking of up to 77% for the load interval tested and up to 90% at lower loads, compared to approaches from the literature. Crosstalk was also reduced in over 36%, on average, and up to 60% at lower loads while fragmentation was mitigated in up to 11%.